Developing the record management and filing structure in the organization using knowledge mapping technique - Saiyed Yeop, Sharifah Fahimah (Persatuan Pustakawan Malaysia, 2014)
Managing records, physical or electronic, are now more challenging as the data and information are overloaded in various types of medium. Information professional, records manager and archivist are facing tremendous challenges to ensure the proper organization, identification, storage, retrieval, circulation and disposal of records in the organization. The awareness on the importance of managing records in many organizations contributed to the failure of most records management initiatives. This paper attempted to document tacit experiences in developing records management and filing structure in the higher learning organization with knowledge mapping technique.